Diabetic foot ulcers: contemporary assessment and management - Zia Ur Rehman; Khan, Junaid; Noordin, Shahryar (Journal of the Pakistan Medical Association, 2023)
Diabetic foot ulcer disease is the combination of vasculopathy, neuropathy and infection. It is important to identify the main aetiology and to treat it for optimal ulcer healing so that limb amputation may be prevented. A literature review spanning five years (2017-2021) was performed to assess the current understanding of these aetiologies and management options for their treatment. Peripheral artery disease is prevalent in patients with diabetes. Before performing any amputations, whether minor or major, vascular supply in these patients needs to be evaluated and, if needed, improved. Diabetic neuropathy is a long-term complication of uncontrolled diabetes. Patients’ education is very important with respect to selfcare and prevention of foot complications arising out of minor trauma in diabetic population. —Continue